Robust adaptive control for spacecraft attitude synchronization subject to external disturbances: A performance adjustable event‐triggered mechanism. (4th December 2022) - Hu, Wenfeng; Li, Zichuang; Dai, Ming‐Zhe; Huang, Tingwen
Summary: This article addresses the leader‐following synchronization problem of multiple rigid spacecraft systems affected by external disturbances with the directed topology. An event‐triggered distributed observer is proposed to estimate the leader's state. By integrating a performance adjustable function (PAF) into the event‐triggered mechanism, the sampling frequency and estimation speed can be adjusted. Based on the event‐triggered distributed observer, an adaptive event‐triggered control scheme is proposed to aganist the external disturbances. With the adaptive event‐triggered control scheme, continuous communication between spacecraft is no longer required and Zeno‐free property can be guaranteed. The effectiveness of the theoretical results is verified by a numerous example.